Advances in Speech-Language Pathology 2017
DOI: 10.5772/intechopen.69743
|View full text |Cite
|
Sign up to set email alerts
|

Response Behaviors in Conversational Speech among Japanese- and English-Speaking Parents and Their Toddlers

Abstract: The present study aimed at exploring the responses of listeners in conversational speech between parents and toddlers. Children's responses toward parents and parents' responses toward children were the focus of this study. Participants included ive dyads each of typically developing two-year-old toddlers and their parents from Japanese-and English-speaking families. Responses of a mother/father toward a child or a child toward a mother/father were classiied into three categories: non-lexical backchannels (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Smaller differences between genders were also observed, in that Sri Lankan and Indian younger males produced more backchannels than female listeners, while the opposite was true for all three groups of older listeners and, to some extent, for the younger British English listeners. Yamashita (2017) investigated backchannels in English and Japanese parent-children conversations and found that the frequencies of backchannels were similar for the two settings, with the adults providing 5 (Japanese) to 14 (English) times more backchannels than the children. The distribution of forms of backchannels differed, with English parents using almost three times more phrasal backchannels than the Japanese, while the latter instead used many more repetitions.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Smaller differences between genders were also observed, in that Sri Lankan and Indian younger males produced more backchannels than female listeners, while the opposite was true for all three groups of older listeners and, to some extent, for the younger British English listeners. Yamashita (2017) investigated backchannels in English and Japanese parent-children conversations and found that the frequencies of backchannels were similar for the two settings, with the adults providing 5 (Japanese) to 14 (English) times more backchannels than the children. The distribution of forms of backchannels differed, with English parents using almost three times more phrasal backchannels than the Japanese, while the latter instead used many more repetitions.…”
Section: Previous Workmentioning
confidence: 99%
“…A large number of studies have demonstrated that distribution and perception of backchannels differ between different cultures and languages ( White, 1989 ; Heinz, 2003 ; Cutrone, 2005 ; Mowlaei, 2017 ; Zellers, 2021 ) and that this may have consequences for intercultural conversation ( White, 1989 ; Wan, 2018 ; Najim and Muhammad, 2020 ), unless the interlocutors adapt to the general backchannel strategy of the language spoken ( Heinz, 2003 ; Cutrone, 2019 ). Other studies have shown that differences in the use and perception of backchannels are also related to gender ( Mulac et al., 1998 ; Stubbe, 1998 ; Ueno, 2008 ), age ( Yamashita, 2017 ; Kraaz and Bernaisch, 2022 ; Bodur et al., 2022 ) and familiarity with the speaker ( Bodur et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation